Monitoring shrimp growth with control charts in aquaculture - Sanchez, Ismael (2021)
The data used in this work was provided by the Ecosac fish farm. The authors wish to express their appreciation for this and for all the support throughout the investigation, especially to the production engineer Grover Cedillo. This research has received financial support from the government of Peru, under contract 49-2018 of the project Proyecto de Mejoramiento y Ampliacion de los Servicios del Sistema Nacional de Ciencia, Tecnologia e Innovacion Tecnologica 8682PE, of the CON-CYTEC/FONDECYT/World Bank Group.